DYNAMICS OF PRE-SERVICE TEACHERS’ EMPLOYABILITY IN 21ST-CENTURY NIGERIA: A FOCUS ON ENGLISH LANGUAGE TEACHERS IN EKITI STATE - Bankole Olagunju Faloye, (JOEL: Journal of Educational and Language Research, 2023)
This research sought to investigate the dynamics involved in employing pre-service English language teachers in public secondary schools in Ekiti State, Nigeria. Specifically, the research investigated the dynamics involved assessment of the applicants’ pedagogical skills, personality and classroom management traits in a 21st-century paradigm. The secondary data emanated from the Practical Teaching Assessment Rating Scale (PTARC) and Oral Competence Test (OCT) on 114 unemployed English language teachers. Four research questions and two hypotheses were formulated and raised to guide the research respectively. The research population consisted of 1,050 graduate English language teachers from Ekiti State University, Ado- Ekiti, College of Education, Ikere Ekiti and the affiliated degree programme of the University of Nigeria, Nsukka. The Ministry of Education, Science and Technology, Ekiti State, selected 114 English language teachers for the examination. The sample size of 114 was derived from the selection process aforementioned. The findings of the study revealed that the English language teachers were employable based on impressive performance in oral and theoretical assessments. The research provides recommendations on the need to include digital interactive courses in oral communication and instruction in spoken English while emphasizing earner-friendly strategies of teaching in Ekiti State public secondary schools